Virtually Ready? Pre-service teachers' perceptions of a virtual internship experience - Stewart Waters; William B. Russell (Research in Social Sciences and Technology- OpenED Network, 2016)
The purpose of this phenomenological study was to understand the experiences of six secondary pre-service teachers that completed a semester long internship with a supervising mentor at a virtual school in the Southeastern United States. The secondary pre-service teachers in this study voluntarily chose a placement in the virtual school over a traditional classroom placement for completion of their initial licensure field experience. This study sought to examine why secondary pre-service teachers chose a virtual internship and what their experiences were like as online instructors. A total of six participants completed a sixty-minute semi-structured interview at the completion of the semester long virtual school internship. Results of the study indicated that secondary pre-service teachers' primary motivation for entering a virtual internship experience was